The social implications of gated communities and the planning process: a suburban case study - Myers, Ashley D. (Kansas State University, 2011)
Gated communities are a growing residential phenomenon in the United States with almost ten percent of households living in gated communities in 2005 (Knox, 2008; Census, 2005). In this study “gated communities” are defined, according to Low (2003), as a residential neighborhood with walls and gates surrounding the development, which excludes non-residents access to all interior amenities including residences, open space, and activities. People are seeking life behind a gate for many reasons, but include the search for security, safety, privacy, prestige, exclusivity, control, and community (Blakely & Snyder, 1999). As this style of development is expanding and as all socio-economic groups want to live in gated communities, cities are beginning to realize gated communities affect all members of the community, not just the ones secluded behind the gate (El Nasser, 2002). After reviewing literature, the author found, the generally accepted social implications and consequences resulting from gated communities were identified as social segregation, loss of community, and division; although, there were also positive results for some people living within gated communities. This report, through a case study format, investigated if the social implications of gated communities are considered during the development review process. Rockwood Falls Estates and Meadows is a suburban gated community and the surrounding local governments, Johnson County and Overland Park, were the object of the case study. The author concluded that gated communities have benefits and concerns. Further, the author found that gated communities can be effectively controlled if the local governments have adopted specific policies dealing with gated communities and implement this policy through specific design review procedures.
Keywords: Gated community; Design review process; Planning process; Local government; Public Policy and Social Welfare (0630); Urban Planning (0999)